The Efficacy of Model-Based Instructions in Teaching Algebra - Alpha Raidin Salibo; Joseph Muñez; Isabelo Bergosa Jr; Rolwen Jay Sumagang; Ken Marviene Gal Ampuan; Alper Vincent D Anggot; Genesis B Naparan (Journal of Elementary and Secondary School, 2026)
Classroom learning relies on engaging teaching approaches. This study focuses on the efficacy of model-based instruction in teaching algebra to 8th-grade students at a public state college located in Tangub City, Misamis Occidental, Philippines, during the school year 2019-2020. Using purposive sampling, 40 students were divided into two groups of 20, each exposed to different teaching approaches. Pre- and post-tests were administered to both groups to assess performance before and after the treatment. To determine the students’ level of performance, the researchers used the Performance Level Assessment Tool, where students’ scores are categorized into five different levels: The Beginning Proficiency Level, the Developing Proficiency Level, the Approaching Proficiency Level, the Proficient Level, and the Advanced Proficiency Level. Mean was also used to determine the performance level of the groups before and after the experiment is conducted. Analysis of Covariance (ANCOVA) was used in determining the impact of teaching with algebraic modelling on students’ performance in Mathematics. The collected data were statistically analyzed using Statistical Package for the Social Sciences (SPSS). The results revealed a significant improvement in the experimental group, with 80% achieving the Advanced Proficiency Level on the post-test, compared to 0% in the control group. The control group showed minimal improvement, with the majority remaining at the Beginning Proficiency Level (75%). ANCOVA confirmed a statistically significant difference (p < .001) in post-test scores between the two groups, favoring the algebraic modelling approach. These findings suggest that model-based instruction, specifically algebraic modelling, significantly enhances student performance in algebra.